2000
DOI: 10.1016/s1350-4177(99)00030-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonication of chitin–glucan, preparation of water-soluble fractions and characterization by HPLC

Abstract: A water-insoluble chitin-glucan complex, isolated from the mycelium of Aspergillus niger, was swollen in various aqueous media and treated subsequently by high-energy sonication. The concentration of the resulting water-soluble polysaccharide fractions was dependent on the swelling medium, the amount of the chitin-glucan complex in the suspension, and on the time of sonication. The yields of water-soluble chitin-glucan were within the range 13.6 to 24.4% relative to the mass of the original chitin-glucan. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 13 publications
0
16
0
2
Order By: Relevance
“…Taking into account previous works [41,42,43,44,45,46], we produced a low-molecular-weight chitin mix (CHL) using combined thermal treatment and sonication on a high-molecular-weight chitin mix (CHH, see the Material and Methods Section). In order to characterize this CHL mix, several analyses were performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account previous works [41,42,43,44,45,46], we produced a low-molecular-weight chitin mix (CHL) using combined thermal treatment and sonication on a high-molecular-weight chitin mix (CHH, see the Material and Methods Section). In order to characterize this CHL mix, several analyses were performed.…”
Section: Resultsmentioning
confidence: 99%
“…The mainstream process for obtaining chitin- or chitosan-derived oligomers involves acid hydrolysis, several deproteinization steps (depending on the natural origin of the chitin), deacetylation and purification by high-performance liquid chromatography, which can lead to the production of oligomers with very high levels of purity. In addition, if chitin oligomers are required, chitosan oligomers need to be re-acetylated [41,42]. As we were interested in producing a mixture of chitin fragments with as high a degree of acetylation as possible and a low molecular weight, we optimized a protocol based on previous work that indicated that chitin biopolymers can be fragmented using sonication.…”
Section: Discussionmentioning
confidence: 99%
“…Tratamento das glucanas bruta e purificada com ultrassom O tratamento com ultrassom e a hidratação da glucana foram realizados segundo Mislovicová et al, 26 com algumas modificações. Utilizou-se uma mistura de 100 mg de glucana (bruta ou purificada) em 25 mL de água, com pH ajustado para 7,0, e submeteu-se ao tratamento com ultrassom (Unique, mod.…”
Section: Figura 1 Procedimento Para O Isolamento Dos Compostos Da Paunclassified
“…Misloviscová et al 26 verificaram que o tratamento da glucanaquitina de Aspergillus niger com ultrassom durante 20 min aumentou a solubilização de carboidratos de 7,6 para 12,2% quando a concentração inicial foi de 50 mg/25 mL. Para a glucana de levedura (Tabela 3) observou-se o aumento na solubilidade de 10,3 para 14,2% quando a glucana purificada foi submetida a um tratamento idêntico.…”
Section: Fraçãounclassified
“…While numerous applications of ultrasound have been published to physically modified chitosan (e.g. to favor its swelling and dissolution [15], to prepare polymeric vesicles [16,17] etc.) to the best of our knowledge no sonochemical modifications of this polysaccharide have been reported to-date.…”
Section: Reactions On Chitosanmentioning
confidence: 99%